2017
DOI: 10.1007/s00439-017-1831-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the genetic relationship between Alzheimer’s disease and cancer using GWAS summary statistics

Abstract: Growing evidence from both epidemiology and basic science suggest an inverse association between Alzheimer’s disease (AD) and cancer. We examined the genetic relationship between AD and various cancer types using GWAS summary statistics from the IGAP and GAME-ON consortia. Sample size ranged from 9,931 to 54,162; SNPs were imputed to the 1000 Genomes European panel. Our results based on cross-trait LD Score regression showed a significant positive genetic correlation between AD and five cancers combined (colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 32 publications
3
38
0
Order By: Relevance
“…Our data suggested that the observed inverse association between dementia and cancer might be a true finding, but the underlying mechanisms are still largely unknown (15). Differential regulation of common genes and pathways might be related to the inverse association between cancer and dementia.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Our data suggested that the observed inverse association between dementia and cancer might be a true finding, but the underlying mechanisms are still largely unknown (15). Differential regulation of common genes and pathways might be related to the inverse association between cancer and dementia.…”
Section: Discussionmentioning
confidence: 67%
“…Survival bias, which means that cancer survivors may be more likely to die before they can develop dementia, has been suggested to confound the observed association (2,14). A potential mechanism is that biological pathway to cancer might be protective against dementia (15)(16)(17)(18), but the existing evidence remains inconclusive. The observed inverse association is further complicated by the medical treatments of various types of cancer, which have been reported to be associated with either a higher or lower risk of dementia (5,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of the genetic overlap between dementia and cancer could reveal the true direction of the association between cancer and dementia. One study used genomewide association study summary statistics showed a positive genetic correlation between these diseases, implying that cancer and dementia share some genetic background . Shared genetic variants could modulate the risk of cancer and dementia in the same direction, thereby pointing towards pleiotropic effects.…”
Section: The Risk Of Cancer In Dementia Patients and The Risk Of Demementioning
confidence: 99%
“…One study used genomewide association study summary statistics showed a positive genetic correlation between these diseases, implying that cancer and dementia share some genetic background. 76 Shared genetic variants could modulate the risk of cancer and dementia in the same direction, thereby pointing towards pleiotropic effects. The strongest positive genetic correlations were found in regions representing enhancer marks on the genome, indicating a possible role of gene expression regulation in the pathogenesis of both diseases.…”
Section: Geneticsmentioning
confidence: 99%
“…Increasing evidence suggest that there are common pathophysiological features in both diseases, such as DNA damage, oxidative stress, mitochondrial dysfunction, metabolic dysregulation, and inflammation (Driver, 2014;Houck et al, 2018). Moreover, single nucleotide polymorphism (SNP)-trait genome-wide association studies (GWAS) have shown positive genetic correlations between AD and cancer (Feng et al, 2017). Although the relationship between AD and cancer remains controversial, the analysis of large cancer multi-omics datasets and associated clinical information should provide insights into developing new drugs for AD.…”
Section: Introductionmentioning
confidence: 99%